Property Ownership and the Neighborhood Community in Early Modern Kyoto - Mary Louise Nagata (L'Atelier du CRH)
What happened to property when the owner died without heir? This study uses the property transmission wills required by Kyoto neighborhoods, a register of property owners that follows the properties through multiple transmissions, documents of sale and lease, and a digitalized file pooling the annual population surveys for thirty neighborhoods between 1842 and 1869, to address this question. These documents and analyses demonstrate what happened to property transmission as a family ran out of heirs and the steps the neighborhood community took to prevent confusion and conflict over property ownership. The sixteenth century history of the rebuilding of Kyoto as an early modern city also reveals the basis for community claims of ownership.